2020
DOI: 10.1101/2020.07.03.20145763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen and mortality in COVID-19 pneumonia: a comparative analysis of supplemental oxygen policies and health outcomes across 26 countries

Abstract: Introduction Hypoxia is the main cause of morbidity and mortality in COVID-19. During the COVID-19 pandemic some countries have reduced access to supplemental oxygen (e.g. oxygen rationing), whereas other nations have maintained and even improved access to supplemental oxygen. We examined whether such variation in the access to supplemental oxygen had any bearing on mortality in COVID-19. Methods Three independent investigators searched for, identified and extracted the nationally recommended target o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Emerging international evidence has indicated that lower thresholds for oxygen saturation, are associated with worse patient outcomes 2 32 . In the case of our review, even though some authors argued that pulse oximetry identified the need for hospitalisation when using a cut-off of 92% 16 , we could not reach conclusions in relation to patient safety and the degree to which remote home monitoring models can conclusively identify cases of deterioration at an earlier stage in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging international evidence has indicated that lower thresholds for oxygen saturation, are associated with worse patient outcomes 2 32 . In the case of our review, even though some authors argued that pulse oximetry identified the need for hospitalisation when using a cut-off of 92% 16 , we could not reach conclusions in relation to patient safety and the degree to which remote home monitoring models can conclusively identify cases of deterioration at an earlier stage in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in the presentation of patients with COVID-19 has led to patients arriving as emergencies with very low oxygen saturations, often without accompanying breathlessness ('silent hypoxia') 1 . These delayed presentations of severe COVID-19 led to extended hospital admissions for patients, often requiring invasive treatment and potential admission to intensive care units (ICU) or death 2 . Remote home monitoring models (sometimes referred to as 'virtual wards') have been established to: 1) avoid unnecessary hospital admissions (appropriate care at the appropriate place), and 2) escalate cases of deterioration at an earlier stage to avoid invasive ventilation and ICU admission 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in the presentation of patients with COVID-19 has led to patients arriving in acute care emergency departments with very low oxygen saturations, often without accompanying breathlessness ('silent hypoxia') [1]. As a result, many patients have been admitted with an advanced course of the disease, requiring extended hospital length of stays, invasive treatment, potential admission to Intensive Care Units (ICU) and death [2]. Remote home monitoring models (sometimes referred to as 'virtual wards'), using pulse oximetery and other measurements (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen is an essential aspect of treatment for patients with COVID-19 pneumonia. Indeed, the major mechanism for injury and death in COVID-19 is related to hypoxia (14).…”
Section: General Characteristics and Clinical Presentationsmentioning
confidence: 99%